Application of Environmental Engineering in Improving Energy Transfer Efficiency - Ridlo, M. Ainur; Anripa, Nuralfin; Purwaningrum, Shintawati Dyah; Agustin, Niyar Candra; Pramono, Susatyo Adhi (Trigin Publisher, 2024)
This research has the main objective of discovering and analysing environmental techniques that are effective in improving energy transfer efficiency. This includes technologies and practices in various sectors such as renewable energy, energy infrastructure, waste management, and building efficiency. The research used a mixed methods approach, combining qualitative as well as quantitative data collection and analysis techniques. The methods used include literature review, surveys, interviews, and statistical modelling to comprehensively explore the research questions from multiple perspectives. The results show a significant positive correlation between education level and income. In addition, there were also significant differences in access to health services between different socioeconomic groups. The findings highlight the importance of interventions to promote equity in education and health. The study concludes that improving access to and quality of education and public health services can contribute significantly to poverty alleviation and reduction of socio-economic disparities. It recommends policies and programmes that focus on investments in these areas to promote more inclusive and sustainable development.